IMPLEMENTASI PENGELOLAAN TENAGA PENDIDIK DI MI. AZ-ZAHIR PALEMBANG - Rachmad Sobri (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2019)
AbstrackThis research is entitled Implementation of Management of Educators in MI Az-Zahir Palembang. With the formulation of the first problem: How is the Implementation of Management of Educators in MI Az-Zahir Palembang? Second: What are the factors that support and hinder the Implementation of Management of Educators in MI Az-Zahir Palembang? The purpose of this study was to find out how the implementation of management of teaching staff at MI Az-Zahir Palembang, to find out what factors support and hinder the implementation of Management of Educators in MI Az-Zahir Palembang. In the study the authors used qualitative research. The informants in this study were the principal of MI Az-Zahir Palembang as the key informant and head of the TU as well as educators as supporting informants. Sources of data in this study are primary data sources in the form of data obtained from the MI Az-Zahir Palembang principal and secondary data obtained from the literature relating to this study including the teaching staff documents. Data collection techniques through observation, interviews, were shown to the MI Az-Zahir Palembang head of the TU head and educators and documentation were used to collect data on the state of the educator's environment etc. Data analysis techniques are done by data reduction, data presentation, and conclusions or data verification. The results showed that the implementation of teaching staff at MI Az-Zahir Palembang from the process of planning, recruitment, selection, orientation, placement and evaluation of teaching staff was quite good. Because the school has carried out the planning process of the teaching staff until the evaluation of the teaching staff, the lack of supervision by the principal is still found by teaching staff not in science and there are still teachers who are only high school graduates, so the process of teaching educators is maximal. The factors that influence the implementation of educators are supporting and inhibiting factors. Supporting factors are the ability of a good headmaster, the competence of teaching staff in accordance with their scientific fields, complete facilities and infrastructure, adequate funding, and school committees that play an active role. Whereas the inhibiting factors for the implementation of teaching staff are the inability of principals to manage educators, the competence of educators who are not in accordance with their knowledge and school needs, incomplete facilities and infrastructure, lack of community participation in the management of educators, and financial financing management. not maximal. AbstrackPenelitian ini berjudul Implementasi Pengelolaan Tenaga Pendidik di MI Az-Zahir Palembang. Dengan rumusan masalah pertama: Bagaimana Implementasi Pengelolaan Tenaga Pendidik di MI Az-Zahir Palembang? Kedua: Apa saja faktor yang mendukung dan menghambat Implementasi Pengelolaan Tenaga Pendidik di MI Az-Zahir Palembang? Adapun tujuan dari penelitian ini adalah untuk mengetahui bagaimana implementasi pengelolaan tenaga pendidik di MI Az-Zahir Palembang, Untuk mengetahui apa saja faktor yang mendukung dan menghambat implementasi Pengelolaan Tenaga Pendidik di MI Az-Zahir Palembang. Dalam penelitian penulis menggunakan penelitian kualitatif. Informan dalam penelitian ini yaitu kepala sekolah MI Az-Zahir Palembang sebagai key informan dan kepala TU serta tenaga pendidik sebagai informan pendukung. Sumber data dalam penelitian ini adalah sumber data primer berupa data yang diperoleh dari kepala sekolah MI Az-Zahir Palembang dan data sekunder diperoleh dari literatur yang berkaitan dengan penelitian ini termasuk dokumen tenaga pendidik. teknik pengumpulan data melalui observasi, wawancara, ditunjukan kepada kepala sekolah MI Az-Zahir Palembang kepala TU serta tenaga pendidik dan dokumentasi digunakan untuk menghimpun data tentang keadaan enaga pendidik dll. Teknik analisis data dilakukan dengan reduksi data, penyajian data, dan kesimpulan atau verifikasi data. Hasil penelitian menunjukan bahwa Implementasi tenaga ppendidik di MI Az-Zahir Palembang dari proses perencanaan, rekrutmen, seleksi, orientasi, penempatan dan evaluasi tenaga pendidik sudah cukup baik. Karena sekolah telah melakukan proses perencanaan tenaga pendidik sampai evaluasi tenaga pendidik, namun kurangnya pengawasan yang dilakukan kepala sekolah masih ditemukan tenaga pendidik yang mengajar bukan pada keilmuannya serta masih ada guru yang hanya tamatan SMA, sehingga proses impelentasi tenaga pendidik blum maksimal. Adapun faktor Faktor yang mempengaruhi implementasi tenaga pendidik berupa faktor pendukung dan penghambat. Faktor pendukung yaitu kemampuan kepala sekolah yang baik, kompetensi tenaga pendidik yang sesuai dengan bidang keilmuannya, sarana dan prasarana yang lengkap, pembiayaan yang memadai, dan komite sekolah yang berperan aktif. Sedangkan faktor penghambat implementasi tenaga pendidik yaitu kurang mampunya kepala sekolah dalam melakukan pengelolaan tenaga pendidik, kompetensi tenaga pendidik yang tidak sesuai dengan keilmuannya dan kebutuhan sekolah, sarana dan prasarana yang belum lengkap, kurangnya peran serta masyarakat dalam pengelolaan tenaga pendidik, dan pengelolaan pembiayaan keuangan yang belum maksimal.Key word: implementasi pengelolaan, dan tenaga pendidik.